Faktor risiko demensia pasca stroke iskemik akut - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Objective of this study are to investigate association between acute ischemic stroke out of therapeutic window with risk of post acute ischemic stroke dementia and to determine which factors that influence association between post acute ischemic stroke dementia with stroke out of therapeutic window. This study is a cohort prospective study of comparing acute ischemic stroke cases out of therapeutic window with control group who are patients of acute ischemic stroke in therapeutic window. Seventy-nine subjects are recruited consecutively among patients acute ischemic stroke who required inclusion criteria and exclusion. They admitted and cared in neurological ward at Sardjito Hospital, Yogyakarta. Seven until ten days after onset stroke, the patien will be given cognitif examination with MMSE (Mini Mental State Examination) test to determine cognitive impairment and vascular dementia is diagnosed using criteria from DSM-IV (Diagnostic and Statistical Manual of Mental Disorders IV). Chi square test for categorical data and t test for continous data are used for bivariate analysisi and logistic regression is used for multivariate analysis. The result of this study were frequency of dementia 62% (49/79) and that of non-dementia 38% (30/79). Mean age of dementia post acute ischemic stroke patient was older than non-dementia (63,57Â± 11,85 vs 56,07 +10,52) (p=0,006), there were no gender differences in risk for post acute ischemic stroke dementia (RR 0,37, 95% Confidence Interval ICI], 0,14 - 1,03). Based on bivariat analysis, demented patients had significantly level of education until elementary (RR 2,47